2021
DOI: 10.3389/fcell.2021.620925
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Relationship Between Regulator of Ribosome Synthesis 1 (RRS1) and Diseases

Abstract: A regulator of ribosome synthesis 1 (RRS1) was discovered in yeast and is mainly localized in the nucleolus and endoplasmic reticulum. It regulates ribosomal protein, RNA biosynthesis, and protein secretion and is closely involved in cellular senescence, cell cycle regulation, transcription, translation, oncogenic transformation etc., Mutations in the RRS1 gene are associated with the occurrence and development of Huntington’s disease and cancer, and overexpression of RRS1 promotes tumor growth and metastasis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…Expression of a core mediator of ribosomal assembly RRS1 was also increased at the protein level (Fig. 2g) (Hua et al, 2021). This was unexpected, since ribosome biogenesis is generally suppressed under stress (Lindstrom et al, 2022; Ni and Buszczak, 2023; Szaflarski et al, 2022), and LONP2-depletion in COS-7 cells resulted in strong reduction in protein synthesis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of a core mediator of ribosomal assembly RRS1 was also increased at the protein level (Fig. 2g) (Hua et al, 2021). This was unexpected, since ribosome biogenesis is generally suppressed under stress (Lindstrom et al, 2022; Ni and Buszczak, 2023; Szaflarski et al, 2022), and LONP2-depletion in COS-7 cells resulted in strong reduction in protein synthesis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the downregulation of lncRNA SET-binding factor 2-antisense RNA1 can upregulate miR-143 and inhibit RRS1 and ultimately restrict the progression of breast cancer ( 50 ). In addition, dysregulation of RRS1 is involved in the development of several malignancies and the progression of various tumors, including papillary thyroid carcinoma, retinoblastoma, and neuroblastoma ( 51 54 ). These studies confirm the key role of RRS1 in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…RRS1 (regulator of ribosome synthesis 1) is principally localized in the nucleolus and endoplasmic reticulum [ 55 ]. Recent studies regarded RRS1 as a tumor promotor and concluded that overexpression of RRS1 could facilitate the growth and metastasis of various tumors [ 56 ]. In the molecular mechanism, RRS1 participates in ribosome biosynthesis and mainly influences chromosomal and telomeric arrangement during the cell cycle [ 57 ].…”
Section: Discussionmentioning
confidence: 99%